Trends and perspectives in modern computational science : lectures presented at the International Conference of Computational Methods in Sciences and Engineering (ICCMSE 2006) : recognised conference by the European Society of Computational Methods in Sciences and Engineering (ESCMSE) /: lectures presented at the International Conference of Computational Methods in Sciences and Engineering (ICCMSE 2006) : recognised conference by the European Society of Computational Methods in Sciences and Engineering (ESCMSE). (2006) - Unknown
No abstract available